Factors Influencing Female Entrepreneurship - Fedosova, Yulia; Balogh, Péter; Katonáné Kovács, Judit (International Journal of Engineering and Management Sciences, 2025)
The following research was conducted with the objective of identifying the factors that influence women to become entrepreneurs. It explores the effectiveness of support mechanisms, including mentorship programs, networking opportunities, access to financial resources, and policy interventions in enhancing the success of female entrepreneurs. Special attention is given to the decision-making threshold concept and the role of self-confidence. A multi-method approach was employed, entailed a comprehensive literature review, a qualitative analysis based on interviews, and a quantitative analysis conducted through surveys. The data obtained from these methods were triangulated to ensure robust insights. The research resulted in a model that illustrates the interrelationship between the scientific, practical and educational approaches. The findings highlight the potential of developing a motivation model for female decision-making in entrepreneurship, identifying key motivators, focusing on economic, social and personal factors with self-confidence as a central concept of study.